32.1k views
3 votes
Need help with this math question

Need help with this math question-example-1
User Actine
by
4.9k points

1 Answer

5 votes

Answer:

(D)
(x(x+3))/(x+1)

Explanation:

Given are the functions:


f(x)=x^(3)-9x and
g(x)=x^(2)-2x-3.

Applying the operations on the given functions, we get


(f(x))/(g(x))=(x^(3)-9x)/(x^(2)-2x-3)

=
(x(x^(2)-9))/(x^(2)-3x+x-3)

=
(x(x+3)(x-3))/(x(x-3)+1(x-3))

=
(x(x+3)(x-3))/((x+1)(x-3))

=
(x(x+3))/(x+1)

Thus,
(f(x))/(g(x))=
(x(x+3))/(x+1)

Hence, option D is correct.